Drop out from mental health treatment in the Saudi national mental health survey. Issue 1 (2nd January 2022) - Alangari, Abdulaziz S.; Knox, Sarah S.; Innes, Kim E.; Kristjansson, Alfgeir L.; Wen, Sijin; Bilal, Lisa; Alhabeeb, Abdulhameed; Al-Subaie, Abdullah S.; Altwaijri, Yasmin A.
Abstract: Objectives: To evaluate the patterns and potential risk factors associated with mental health treatment dropout in the Saudi National Mental Health Survey (SNMHS). Methods: The SNMHS is a face-to-face community-based epidemiological survey in a nationally representative household sample of respondents aged 15–65 in the Kingdom of Saudi Arabia (KSA) ( n = 4, 004). The sample was limited to those who had received any type of mental health treatment during the past year ( n = 168). The distribution of service use and the number of visits were examined. Predictors of treatment dropout were analyzed using logistic regression models. Results: Treatment drop out rate was very high overall (42.1%), with dropout occurring early (after 2 visits) in the majority of cases. Participants who were previously married or were diagnosed with a 12-month substance use disorder were significantly more likely than other participants to drop out. Those receiving care from more than three types of providers were significantly less likely than others to terminate treatment prematurely. Conclusions: The rate of premature termination of treatment was high and positively associated with previously married status and substance use and inversely related to the number of different providers and number of visits.